2017
DOI: 10.1093/ee/nvx080
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Platygastridae in Leaf Litter and Understory Layers of Tropical Rainforests of the Western Ghats Biodiversity Hotspot, India

Abstract: Platygastridae is the third largest family of parasitic Hymenoptera in the world. It includes important egg and larval parasitoids of insects and spiders. Therefore, Platygastridae is functionally important in maintaining the stability of tropical rainforests and agroecosystems. Although the diversity of Platygastridae is relatively well-known in agroecosystems, we know little about their diversity in tropical rainforests, and particularly about that of the leaf litter layer. Here, we address the importance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…They have a thick bed of continuous leaf litter on the forest floor and a continuous closed canopy. They are also important centers of insect diversity, including insect functional diversity 35 , 37 , 38 . The sources of natural dung in SGs include macaques ( Macaca radiata E. Geoffroy Saint-Hilaire, 1812), Brown-Palm Civets ( Paradoxurus hermaphroditus Pallas, 1777), bats ( Pteropus spp Brisson, 1762), wild boars ( Sus scrofa Linnaeus, 1758), and sometimes the free-ranging livestock animals, such as cattle, buffalo, goats, dogs, cats, and even chicken (personal observation).…”
Section: Methodsmentioning
confidence: 99%
“…They have a thick bed of continuous leaf litter on the forest floor and a continuous closed canopy. They are also important centers of insect diversity, including insect functional diversity 35 , 37 , 38 . The sources of natural dung in SGs include macaques ( Macaca radiata E. Geoffroy Saint-Hilaire, 1812), Brown-Palm Civets ( Paradoxurus hermaphroditus Pallas, 1777), bats ( Pteropus spp Brisson, 1762), wild boars ( Sus scrofa Linnaeus, 1758), and sometimes the free-ranging livestock animals, such as cattle, buffalo, goats, dogs, cats, and even chicken (personal observation).…”
Section: Methodsmentioning
confidence: 99%
“…Sacred groves are the last refugia of wildlife in the rural and urban environments outside the protected area network. Our study showed that the sacred groves still conserve some data-deficient and rare species in our neighbourhood 8 . We recommend increased local participation from local communities, village authorities, temple trusts, and forest departments to conserve sacred groves of India as a living natural and cultural heritage of India 4 .…”
mentioning
confidence: 63%
“…Today Kerala has about 1200 sacred groves, that are mostly seen in coastal plains of Alappuzha district and in north Malabar region 6 . Unlike the rich knowledge available on plant biodiversity of the sacred groves 3,7 , little is known about the animal biodiversity of sacred groves 8 and how environmental degradation is affecting its biodiversity.…”
mentioning
confidence: 99%
See 2 more Smart Citations